MALDI mass spectrometry of zirconium and hafnium dibenzoylmethanate phthalocyanines - Chernii, V.Ya.; Severinovskaya, O.V.; Kovalska, V.B.; Tretyakova, I.N.; Losytskyy, M.Yu.; Yarmoluk, S.M.; Volkov, S.V. (Украинский химический журнал, 2012)
The GALDI mass spectrometry studies have shown the noticeable distinction in behavior of similar structure phthalocyanine complexes of zirconium and hafnium containing dibenzoylmethane groups as out-of-plane ligands. The hafnium phthalocyanine PcHfDbm₂ is an association prone and form different types of associates ([(PcHfDbm)₂]⁺, [PcHfDbm+PcHfDbm₂]⁺) in positive ion mode and ([(PcHfDbm₂)₂]⁻) in negative ion mode, while for zirconium phthalocyanine PcZrDbm₂ no associates were observed. Furthermore two pathways of fragmentation are suggested for these complexes. The first pathway occurs for both PcZrDbm₂ and PcHfDbm₂ in positive and negative ion modes, while second one only for PcHfDbm₂ in negative ion mode. Interaction of phthalocyanines with fibrillogenic protein insulin was studied by MALDI mass spectrometry. In presence of PcZrDbm₂ and PcHfDbm₂ the disappearance of peaks of low-molecular aggregates of insulin is observed, that points at interaction of phthalocyanines with protein early aggregates.